2001
DOI: 10.1007/bf02946113
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aflatoxins in selected colombian foods

Abstract: A survey of aflatoxin contamination in selected Colombian foods was conducted over a 12-month period on a total of 248 samples. Samples were collected in supermarkets, retail stores and stock centres and were grouped into five categories: (1) corn and corn products, (2) cereal grains, (3) rice and rice products, (4) legume seeds; and (5) snacks and breakfast cereals. Aflatoxins were identified and quantitated using a liquid chromatographic technique with a limit of detection of 1 ng/g for each aflatoxin. Aflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
0
15
2
4
Order By: Relevance
“…Incidence of aflatoxin B 1 was also found to be significant in rice samples in Malaysia (Abdullah et al 1998;Ali 2000), Columbia (Diaz et al 2001), United Arab Emirates (Osman et al 1999) and Thailand (Suprasert 2000). However, in Korea of the 88 samples analysed in 2002, only five samples Aflatoxin B 1 contamination in parboiled rice samples in India: A multicentre study 413 contained AFB 1 in the range of 2.1-7.7 mg kg À1 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Incidence of aflatoxin B 1 was also found to be significant in rice samples in Malaysia (Abdullah et al 1998;Ali 2000), Columbia (Diaz et al 2001), United Arab Emirates (Osman et al 1999) and Thailand (Suprasert 2000). However, in Korea of the 88 samples analysed in 2002, only five samples Aflatoxin B 1 contamination in parboiled rice samples in India: A multicentre study 413 contained AFB 1 in the range of 2.1-7.7 mg kg À1 .…”
Section: Resultsmentioning
confidence: 81%
“…The incidence and level of aflatoxin contamination has been reported in rice samples from several countries like Korea, Malaysia, Columbia, United Arab Emirates, Thailand etc. (Palmgreen and Hages 1987;Abdullah et al 1998;Pittet 1998;Osman et al 1999;Ali 2000;Suprasert 2000;Diaz et al 2001;Moss 2002). However, only two studies restricted to few locations have so far been carried out in India to assess the incidence of aflatoxin B 1 in paddy/milled white rice (Bhat et al 1978;Bilgrami and Sinha 1984).…”
Section: Introductionmentioning
confidence: 94%
“…The incidence and level of aflatoxin contamination in rice, the major staple food in many Asian countries including Korea, have been reported world-wide (Abdullah et al 1998, Pittet 1998, Bhat and Vasanthi 1999, Osman et al 1999, Ali 2000, Suprasert 2000, Diaz et al 2001, Moss 2002. In previous surveys (Kim et al 2000, Park et al 2002, the presence of aflatoxin has been reported in barley-and corn-based foods as well as in dairy products and Korean traditional soybean, meju (crushed soybean cake fermented by using natural microflora).…”
Section: Introductionmentioning
confidence: 90%
“…The four experimental treatments consisted of the same mash broiler starter ration modified as described below. The experimental diet was analyzed for aflatoxins B1, B2, G1 and G2 (Diaz et al, 2001), DON (Trucksess et al, 1998), zearalenone (Diaz and Céspedes, 1997), T-2 toxin and HT-2 toxin (Pascale et al, 2003) and no detectable levels of any of these mycotoxins were found. The experimental groups were; Group 1: negative control, no T-2 toxin or additive; group 2: Mycofix-S, 2.5g/kg; group 3: positive control, 2.5 ppm T-2 toxin; group 4: 2.5 ppm T-2 toxin + 2.5g/kg Mycofix-S. Feed and water were provided ad libitum for 28 days (days 1 to 28 of age).…”
Section: Methodsmentioning
confidence: 99%